High Lead Exposure Associated With Higher Blood Pressure in Haiti: a Warning Sign for Low-Income Countries. Issue 1 (January 2022) - Yan, Lily D.; Rouzier, Vanessa; Pierre, Jean Lookens; Lee, Myung Hee; Muntner, Paul; Parsons, Patrick J.; Apollon, Alexandra; St-Preux, Stephano; Malebranche, Rodolphe; Pierre, Gerard; Emmanuel, Evens; Nash, Denis; et al.
Abstract : Cardiovascular disease is the leading cause of death in lower-income countries including Haiti. Environmental lead exposure is associated with high blood pressure and cardiovascular mortality in high-income countries but has not been systematically measured and evaluated as a potential modifiable cardiovascular risk factor in lower-income countries where 6.5 billion people reside. We hypothesized lead exposure is high in urban Haiti and associated with higher blood pressure levels. Blood lead levels were measured in 2504 participants ≥18 years enrolled in a longitudinal population-based cohort study in Port-au-Prince. Lead screening was conducted using LeadCare II (detection limit ≥3.3 µg/dL). Levels below detection were imputed by dividing the level of detection by √2. Associations between lead (quartiles) and systolic blood pressure and diastolic blood pressure were assessed, adjusting for age, sex, obesity, smoking, alcohol, physical activity, income, and antihypertensive medication use. The median age of participants was 40 years and 60.1% were female. The geometric mean blood lead level was 4.73µg/dL, 71.1% had a detectable lead level and 42.3% had a blood lead level ≥5 µg/dL. After multivariable adjustment, lead levels in quartile four (≥6.5 µg/dL) compared with quartile 1 (<3.4 µg/dL) were associated with 2.42 mm Hg (95% CI, 0.36–4.49) higher systolic blood pressure and 1.96 mm Hg (95% CI, 0.56–3.37) higher diastolic blood pressure. In conclusion, widespread environmental lead exposure is evident in urban Haiti, with higher lead levels associated with higher systolic and diastolic blood pressure. Lead is a current and potentially modifiable pollutant in lower-income countries that warrants urgent public health remediation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03892265. Abstract : Supplemental Digital Content is available in the text.